Télévision et apprentissage de l'italien dans un contexte plurilingue : pistes pour l'enseignement des langues étrangères à l'école élémentaire - Jean‑Paul Narcy‑Combes; Amel Boughnim (Recherches en didactique des langues et des cultures)
The specific situation of Tunisian TV viewers who acquired Italian by simply watching RAI Uno programmes between 1960 and the end of the 1990's suggests new approaches to the teaching of languages in French primary schools. This specific experience will first be described with special insistence on contributing factors such as knowledge of schemata, availability of comprehensible input thanks to the visual element and the effect of the plurilingual experience of the informants on their acquisition of Italian. The results suggest new ways of leading children to acquire languages by relying on adequate tasks, with or without language production, especially in settings where teachers are not specialists of the language that is being learnt.